Effect of Plant Density and Harvest Data on Some Seeds Quality Characteristics of Pea Crop Pisum sativum L. var. Progress No.9 - Aisha Ellafi; Ahmed Fateh Ayad; Abdul Majeed Zaghdani (AlQalam Journal of Medical and Applied Sciences, 2024)
An Experiment was conducted to investigate the effect of plant density and harvest dates on some characteristics of pea seeds quality Pisum sativum var. Progress No. 9, at the National Center for Multiplication and Handling of Improved Seeds Station in Sidi Al-Masry, Tripoli, Libya. The experiment was laid out in RCBD Design with two factors, seed distances within row 10,20 and 30 cm and two harvest dates with three replicates each. Recorded data were weight of a thousand seeds gram, the degree of electrical conductivity of the seeds soak μmos/cm/g, germination percentage, and the protein percentage of the seeds. Results showed that there were no significant effects(P<0.05) of planting distances on seed germination percentage, while the weight of one thousand seeds increased significantly (P<0.05) from 304.9 to 310.7 gram with increasing in planting distances from 10 to 30 cm, respectively. Electrical conductivity of the soak seeds decreased from 17.908 to 14.726 μmos/cm/g, with the increase in plant distance from 10 to 30 cm respectively. Chemical seed analysis showed that there was a significant increase (P<0.05) in protein seed percentages from 20.3 to 23.1%. with increasing in planting distances from 10 to 30 cm, respectively. Results showed that the see quality parameters were significantly affected (P<0.05) by harvest date, weight of 1000 seeds increased from 302.7 to 311.2-gram, electrical conductivity of the seed infusion were 19.478 and 13.743 µmos/cm/g, percentage of seed germination were 96.4 and 98.08%, and the seed protein percentage were 20.4 and 23.4% at early and late harvest, respectively. The results showed that interaction between planting distances and harvest date did not have a significant effect (P<0.05) in seed percentage germination and degree of electrical conductivity of the seed infusion, but it has a significance effect (P<0.05) on weight of 1000 seeds. أجريت التجربة لمعرفة تأثير الكثافة النباتية وموعد الحصاد في بعض خصائص جودة بذور البازلاء بمحطة المركز الوطني لإكثار وتداول البذور المحسنة بسيدي المصري- طرابلس، ليبيا. تم تنفيذ التجربة بتصميم القطاعات العشوائية الكاملة بثلاثة مكررات، حيث اشتملت الدراسة على عاملين الأول المسافة الزراعة والعامل الثاني موعدي الحصاد المبكر والمتأخر، ومن هذه الخصائص المدروسة وزن الألف بذرة(جم) ودرجة التوصيل الكهربائي لمنقوع البذور(ميكروموز/سم/جم) ، ونسبة الإنبات (%)، ونسبة البروتين لبذور(%). بينت نتائج الدراسة إلى عدم وجود تأثيرات معنوية (P<0.05) لمسافات الزراعة على نسبة إنبات البذور، بينما زاد وزن الألف بذرة معنوياً (P<0.05) من 304.9 إلى 310.7 جرام بزيادة مسافات الزراعة من 10 إلى 30 سم على التوالي، وانخفضت درجة التوصيل الكهربائي لمنقوع البذور من 17.908 إلى 14.726 ميكروموز/سم/جم بزيادة مسافة الزراعة من 10 إلى 30 سم على االتوالي، وأظهرالتحليل الكيميائي للبذور إن هناك زيادة معنوية (P<0.05) في النسبة المئوية لبروتين البذورمن 20.3 % إلى 23.1% مع زيادة مسافات الزراعة من 10 إلى 30 سم على التوالي. أظهرت النتائج أن مؤشرات الجودة قد تأثرت معنوياً (P<0.05) بموعد الحصاد، حيث زاد وزن الألف بذرة 302.7 و 311.2جرام، وكانت درجة التوصيل الكهربائي لمنقوع البذور 19.478 و 13.743 ميكروموز/سم/ جم، والنسبة المئوية لإنبات البذور 96.42 و 98.08 % ولبروتين البذور 20.4 و 23.4 % عند الحصاد المبكر و المتأخر على التوالي. أوضحت النتائج أن للتداخل بين مسافات الزراعة وموعد الحصاد لم يؤدي إلى إحداث نتائج معنوية في النسبة المئوية لإنبات البذور و درجة التوصيل الكهربائي لمنقوع البذور، ولكن كان التأثير المعنوي (P<0.05) في وزن الألف بذرة.